Does Innovation Affect Company Performance? Exploring the Mediation Effects of Management Accounting Information Systems - Desrir Miftah; Julina Julina (Universitas Prasetiya Mulya, 2020)
This study attempt to determine the direct effect of innovation on company performance and its indirect effect through Management Accounting Information Systems (MAIS) as an mediating/intervening variable. Samples were managers in the manufacturing industry that produces Crude Palm Oil (CPO) operating in Riau Province. Data collected through questionnaires and processed using SEM-PLS. The results found that innovation affects firm performance. Management Accounting Information Systems mediates the effect of innovation and firm performance. Research on MAIS as intervening variable in the palm oil industry was first carried out especially in Indonesia. Innovations made by company through a good Management Accounting Information System will improve the performance of CPO producing company.Keywords: Company performance, Innovation, Management accouting information systems.* Departement of Accounting, State Islamic University of Sultan Syarif Kasim Riau Jalan HR. Soebrantas Km. 15 No. 155, Panam, Kec. Tampan, Kota Pekanbaru, Riau, 28293 https://doi.org/10.21632/irjbs.13.2.189-200